Analisis kecemasan dan motivasi pada atlet panjat dinding nomor speed FPTI Jawa Barat - Zuri, Alpian; Kusumawati, Mia (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam 45, 2022)
Climbing athletes can climb quickly when practicing, but when facing competitions these athletes cannot show maximum performance. Climbing speed when practicing is better than when competing. Athletes in reality are too anxious when facing a match so that expectations that should be achieved easily become difficult, another example that emphasizes that the role of mental aspects is one of the other aspects such as physical, technical, strategic and tactical aspects that determine the appearance of athletes in the match. This study aims to determine the level of anxiety and motivation of West Java FPTI speed wall climbing athletes. The research method used is descriptive research method with correlation technique, the sample of this research is the West Java contingent PON training team with a total sample of 15 athletes with sampling techniques using purposive sampling. The research instruments are the Sport Competition Anxiety Test (SCAT) for Anxiety, Sport Motivation Scale (SMS) for motivation, and Speed World Record Best Time for Speed Number climbing. Data analysis uses descriptive data with a significant level of 0.05. The results showed that the level of anxiety of speed number athletes was 89.5% and the level of motivation of speed number athletes was 74%. For further research, psycholigists are needed in the field of sports to develop psychological aspects that are important for athletes.